Improvement of the communication between teachers and students in the coaching programme and in a process of action research - Lory, Michal (Economics and Business Review, 2015)
The paper seeks to explain the process of the coaching programme for teachers in elementary 3 schools in Israel in an action research, for the improvement of the communication between the students and teachers. The objective of the present research is to launch a group coaching programme amongst fellow teachers in the school, including to design and examine this experience in the format of an action research with emphasis on the potential influence of the nature of the communication between the teachers and students and as a result on the academic achievement of the students.The research presented in this paper is based on the qualitative and quantitative research approaches. The validation of the research findings is performed primarily on the basis of triangulation between the interviews held with a group of teachers and the personal questionnaires4 distributed to the teachers and their analysis [Ellis, Adams, and Bochner 2011].